Complete mitochondrial genome sequence of Aspergillus flavus SRRC1009: insight of intraspecific variations on A. flavus mitochondrial genomes. Issue 3 (2nd July 2020) - Park, Jongsun; Lee, Mi-Kyung; Yu, Jae-Hyuk; Zhu, Bohan; Kim, Jong-Hwa; Han, Kap-Hoon
Abstract: The mitogenome of Aspergillus flavus SRRC1009 was sequenced to investigate intraspecific variations on mitochondrial genomes of A. flavus . It shows 29, 202 bp with a typical configuration of Aspergillus mitogenome. Sixteen SNPs and 22 INDELs and 17 SNPs and 27 INDELs were identified against AflaGuard ® and JQ355000, respectively. Phylogenetic trees present in the three A. flavus mitochondrial genomes were clustered with A. oryzae mitochondrial genome in one clade.